Assessment of quality of life among stroke survivors: a longitudinal study - Rajan, Babitha; Pruthvish, S.; Lalitha, K.; Tyloth, Murali; Murthy, N. S. (International Journal Of Community Medicine And Public Health, 2019)
Background: Quality of life (QoL) among stroke survivors is a concern which has not received sufficient attention in India. The objective of the study was to assess the quality of life of stroke survivors in rural population of Chikkaballapur district, Karnataka. Methods: A community based longitudinal study was done amongst the 150 incident stroke cases registered during the period from March 2013 to November 2014 and who survived beyond 28 days. The cases were enrolled and interviewed using a semi-structured questionnaire and were followed up for 6th month period. QoL was assessed at baseline (at 28 days), at 3rd month and 6th Month using Stroke Specific QoL scale (SSQoL) and Barthel index (BI). Results: The mean age of the persons with stroke was 61.3±15 years with a majority being males (69.3%). Baseline median score (IQR) of SSQoL at 28th day was poor i.e. 131 (77-183). Among the 150 cases, 136 (91%) survived until the end of 6th month. The overall QOL gradually improved to 182 (133-213) and 185 (147-213) at 3rd and 6th month respectively and similar improvement was seen individually in physical, psychological and social domains as well and on multivariate logistic regression age <60 years and few disturbed consciousness among the stroke survivors during the 6th month follow up were found to be predictors for improved quality of life. Conclusions: QoL showed significant improvements in all physical, psychological and social domains by the end of the 6th month of follow up.